EFEKTIVITAS PEMBERIAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BROKOLI (Brassica oleracea var. italica) - Arifin, Tuti Handayani (Agriculture Faculty of Flores University, 2026)
Efforts to increase the production and yield of broccoli plants are by providing adequate nutrition, one of which is by providing chicken manure. This research aims to determine the effect of giving chicken manure on the growth and yield of broccoli plants. The research was carried out on community land, Kec. Camba Maros Regency, South Sulawesi in May – August 2024. This research design used a Randomized Group Design (RAK) with five treatment doses, namely P0 (without manure), P1 (1 kg chicken manure/polybag), P2 (2 kg chicken manure/polybag), P3 (3 kg chicken manure/polybag), P4 (4 kg chicken manure/polybag). Each treatment was repeated three times. The results of the research show that the best dose of chicken manure is P4 or 4 kg. Giving treatment with a dose of chicken manure of 4 kg resulted in higher plant height, number of leaves, fresh weight and flower diameter of broccoli plants compared to treatment with doses of chicken manure of 1 kg, 2 kg and 3 kg.